2021
DOI: 10.3390/jof7090745
|View full text |Cite
|
Sign up to set email alerts
|

Native Endophytic Pseudomonas putida as a Biocontrol Agent against Common Bean Rust Caused by Uromyces appendiculatus

Abstract: This study aimed to evaluate the efficacy of endophytic bacterium to control common bean rust disease under greenhouse conditions. Endophytic bacterium Pseudomonas putida ASU15 was isolated from fresh asymptomatic common bean, identified using biochemical and molecular characteristics. In vitro, the inhibitory effect of different concentrations of P. putida (1 × 104, 1 × 105 and 1 × 106), as well as fungicide ortiva (0.01%) on uredospores germination of Uromyces appendiculatus were tested using water agar medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Mizubuti et al (1995) and Zyton and Hassan (2017) tested the ability of the tested bio-agents, B. subtilis and B. thuringiensis and significantly caused reduction in the germination of U. appendiculatus uredospores. The obtained data also are in harmony with those reported by Ismail and Afifi (2019) and Abo-Elyousr et al (2021) who indicated that uredospore germination of U. appendiculatus in vitro were affected by the biotic and abiotic factors, also these results agree with those obtained by Abeysinghe (2009) who mentioned that the use of rhizobacteria reduce U. appendiculatus uredospore germination.…”
Section: Discussionsupporting
confidence: 91%
“…Mizubuti et al (1995) and Zyton and Hassan (2017) tested the ability of the tested bio-agents, B. subtilis and B. thuringiensis and significantly caused reduction in the germination of U. appendiculatus uredospores. The obtained data also are in harmony with those reported by Ismail and Afifi (2019) and Abo-Elyousr et al (2021) who indicated that uredospore germination of U. appendiculatus in vitro were affected by the biotic and abiotic factors, also these results agree with those obtained by Abeysinghe (2009) who mentioned that the use of rhizobacteria reduce U. appendiculatus uredospore germination.…”
Section: Discussionsupporting
confidence: 91%
“…The selected isolates could be 10 grouped into four genera, i.e., Bacillus (4 strains), Klebsiella (1 strain), Pseudomonas (2 strains) and Xanthomonas (1 strain). Similarly, other researchers have done reports about the isolation of endophytic bacteria from maize, 27 carrots, 28 common bean, 29,30 and sugar beet. 31 There was significant diversity in the types of endophytes bacteria, both genotypic and phenotypic.…”
Section: Discussionmentioning
confidence: 96%
“…Endophytic B. subtilis, B. velezensis, Leuconostoc mesenteroides , and Lactococcus lactis were capable of controlling the bacterial wilt of tomato (Dowarah et al, 2021 ). Native endophytic P. putida afforded a significant reduction in common bean rust caused by Uromyces appendiculatus (Abo-Elyousr et al, 2021 ). In the current study, 20 out of 124 bacterial endophytes exhibited good antagonistic activities against S. rolfsii and F. oxysporum both in vitro and on root slices ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chitinophaga and Flavobacterium were enriched by sugar beet to suppress the root pathogen Rhizoctonia solani (Carrion et al, 2019 ). The mechanisms for plant growth promotion by bacterial endophytes involve the acquisition of nutrients such as nitrogen, phosphate, potassium, and iron and the production of plant hormones such as auxin, cytokinin, or ethylene (Santoyo et al, 2016 ; Wu et al, 2021 ), while the production of hydrolytic enzymes and antimicrobial metabolites such as antibiosis and volatile organic compounds and induction of systemic resistance are mechanisms employed by bacterial endophytes for plant protection against pathogens (Abo-Elyousr et al, 2021 ; Wang et al, 2021 ; Dimkić et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%